Modern digitization and its expected impact on the efficiency of Islamic financial transactions in Libya - Islio, Hamida AbdelAziz Ali; Dabou, Muhammad Ahmed Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
This research paper discusses the need of Islamic banks to follow a modern electronic digitization system, free of suspicion and legal warnings in their Islamic financial transactions, to show their true potential in meeting the needs of customers of electronic development, and in the direction of keeping pace with modern technology witnessed in the world. The results showed that the establishment of Islamic banks in Libya needs a tight strategy based on the provisions and rules of Islamic Sharia, to keep pace with modern technological developments, represented in modern electronic digitization, which meets the needs of customers, as well as the lack of awareness of the capabilities that distinguish Islamic banks in their ability to deal with any advanced electronic system accident.